2014
DOI: 10.1007/s10823-014-9251-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Health Inequalities Among the Older Population in India: A Decomposition Analysis

Abstract: This study quantified and decomposed health inequalities among the older population in India and analyzes how health status varies for populations between 60 to 69 years and 70 years and above. Data from the 60th round of the National Sample Survey (NSS) was used for the analyses. Socioeconomic inequalities in health status were measured by using Concentration Index (CI) and further decomposed to find critical determinants and their relative contributions to total health inequality. Overall, CI estimates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…The findings of the present study are generally in line with other studies decomposing income inequalities in mental health, in Europe [5,23], North America [31] and in low- and middle-income countries [3234], pointing out the existence of inequalities disfavoring the less affluent population. Although it is hazardous to make a straight comparison between the Cs, it should be noted that the magnitude of inequalities in mental health in the present study is larger than that reported in a former study conducted in Europe [23].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study are generally in line with other studies decomposing income inequalities in mental health, in Europe [5,23], North America [31] and in low- and middle-income countries [3234], pointing out the existence of inequalities disfavoring the less affluent population. Although it is hazardous to make a straight comparison between the Cs, it should be noted that the magnitude of inequalities in mental health in the present study is larger than that reported in a former study conducted in Europe [23].…”
Section: Discussionsupporting
confidence: 92%
“…The concentration index has been widely used for measuring income-related inequalities in the health sector internationally, whilst its decomposition analysis has been increasingly adopted to study inequality determinants [1113]. The majority of previous studies investigated health utilization inequality in China, with very limited study focused on health status [12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the older people tend to have fewer resources available to pay for health care (Freedman et al, 2004;Yadav et al, 2011;Goli et al, 2012). As the population ageing continues in India, the likeliest tendency is that the demand to access paid care and assistive technology will increase.…”
Section: Socioeconomic Differentials In the Burden Of Multiple Disabimentioning
confidence: 99%
“…As the population ageing continues in India, the likeliest tendency is that the demand to access paid care and assistive technology will increase. Thus, the disparity among the socioeconomic group will be the factor to reckon with, when a serious attempt is being made to reduce the potential of negative impact of population aging on labor Assessment of socioeconomic differentials productivity (Goli et al, 2012). Therefore, the assessment of disability by socioeconomic characteristics is critical in identifying the vulnerable groups and to make needs based assessment.…”
Section: Socioeconomic Differentials In the Burden Of Multiple Disabimentioning
confidence: 99%